Oral Hygiene Measures to Improve The Condition of Patients With Oral Thrush: A Case Study by. Z And By. I - Zaitun, Zaitun; Yuliani, Ayu; Eka Putri, Salsabila (Jurnal Medisci, 2025)
Background. Babies at a young age are susceptible to diseases. Immunity that has not yet been formed makes it easier for babies to be infected with bacteria or fungi. One of them that often occurs is oral thrush infection. According to research conducted by Eranika in 2016, in Indonesia around 2.4 million babies are experiencing oral thrush. There are many ways to deal with oral thrush, and one way is to maintain oral health by using oral hygiene treatments. Consistent oral hygiene measures in babies will reduce oral thrush so that the impact does not cause serious problems. Aims. To assess the results of oral hygiene measures on improving the condition of patients with oral thrush. Method. Using the descriptive case study method. The subjects used in this case study were two babies with oral thrush. The data collection technique uses interview, observation, and documentation study techniques. Results. The study was carried out on babies with the same complaints. Both have a nursing diagnosis of oral mucosal membrane disorders. The intervention carried out was oral hygiene measures. After 5 days of implementation, there were significant changes in both subjects. Drinking improved, they were not fussy, the oral mucosa was moist, and white plaques were reduced and cleaned. Conclusion. Oral hygiene significantly influences overcoming oral thrush in the baby's mouth. Implementation. Families are advised to routinely check with health services for signs of infection in the mouth.